The current research trends on waqf in social development: a thematic review / Nurul Aien Abd Aziz, Noraina Mazuin Sapuan and Puteri Fadzline Muhamad Tamyez - Abd Aziz, Nurul Aien; Sapuan, Noraina Mazuin; Muhamad Tamyez, Puteri Fadzline (UiTM Cawangan Johor, 2025)
Waqf Involves the dedication of assets or ,wealth for charitable purposes. The development of waqf has significantly contributed to social progress, encompassing various domains such as health, education, poverty alleviation, and business development. Despite its vast potential, waqf remains underemphasied in its role in economic development, raising concerns regarding its impact on advancing the welfare of the ummah and broader economic growth. his study reviews articles published between 2019 and 2024 to explore research therends concerning waqfs role in social development. Employing a thematic review-i v (I'R) methodology, the research incorporates key, words such as "health, 11 "education, 11 "economics, 11 and "business" sourced from the Scopus and Web of Science (WoS) databases. The thematic analysis re11eals five principal themes: Corporate and economic development through Waqf, Sustainability and innovation in Waqf, Challenges and issues in waqf management, Legal and regulatory aspects of Waqf, and Technology application in Waqf. These findings offer valuable insights for researchers and practitioners by enhancing their understanding of how waqf can be more effectively integrated into various social and economic development sectors.